Hierarchical Control on Polyene Macrolide Biosynthesis: PimR Modulates Pimaricin Production via the PAS-LuxR Transcriptional Activator PimM - Santos-Aberturas, Javier; Vicente, Cláudia M.; Payero, Tamara D.; Martín-Sánchez, Lara; Cañibano, Carmen; Martín, Juan F.; Aparicio, Jesús F. (PLOS ONE, 2012)
Control of polyene macrolide production in Streptomyces natalensis is mediated by the transcriptional activator PimR. This regulator combines an N-terminal domain corresponding to the Streptomyces antibiotic regulatory protein (SARP) family of transcriptional activators with a C-terminal half homologous to guanylate cyclases and large ATP-binding regulators of the LuxR family. The PimR SARP domain (PimRSARP) was expressed in Escherichia coli as a glutathione S-transferase (GST)–fused protein. Electrophoretic mobility shift assays showed that GST-PimRSARP binds a single target, the intergenic region between the regulatory genes pimR and pimMs in the pimaricin cluster. The PimRSARP-binding site was investigated by DNaseI protection studies, revealing that it contains three heptameric direct repeats adjusting to the consensus 5′-CGGCAAG-3′. Transcription start points of pimM and pimR promoters were identified by 5′-RACE, revealing that unlike other SARPs, PimRSARP does not interact with the -35 region of its target promoter. Quantitative transcriptional analysis of these regulatory genes on mutants on each of them has allowed the identification of the pimM promoter as the transcriptional target for PimR. Furthermore, the constitutive expression of pimM restored pimaricin production in a pimaricin-deficient strain carrying a deletion mutant of pimR. These results reveal that PimR exerts its positive effect on pimaricin production by controlling pimM expression level, a regulator whose gene product activates transcription from eight different promoters of pimaricin structural genes directly.